Hubungan Sosial Ekonomi Orang Tua Tunggal Dengan Frekuensi Makan Dan Status Gizi Remaja - Yessy Nur Endah Sary (Oksitosin : Jurnal Ilmiah Kebidanan, 2021)
Parental status as a single parent affects the foster pattern of young children who have an impact on child nutrition status. The pattern of the mother's feeding to the child is influenced by education, knowledge of nutrition, economics, family support and employment. The purpose of this study was to analyze the socio-economic relationship of single parents with the frequency of eating and adolescent nutritional status. The study population was a teenager (son/daughter) aged 14-16 to 91 people. Sampling technique with simple random sampling. Inclusion criteria were teenagers (sons/daughters) who do not live in huts, single parents (father alone or mother only). Samples in the study of 87 people. The instruments used for research are brief questionnaires about demographic data (adolescence, single parents, single parent causes, parental education, parental work). Questionnaire for special data frequency meal in a day. Observation sheet to analyze the weight and height of teenagers. Analysis of research data using Chi Square. The results showed that the acquired value P = 0,000 means there is a relationship between the social economy of a single parent with the frequency of adolescent eating and P = 0,003 means there is a relationship between a single parent social economy with a nutritional status of teenagers. Keywords: Socio-Economic, Single Parents, Eating Frequency, Adolescent Nutritional Status ABSTRAK Status orang tua tunggal mempengaruhi pola asuh terhadap anak yang beranjak remaja yang berdampak kepada status gizi anak. Pola pemberian makan orang tua kepada anak dipengaruhi oleh tingkat sosial ekonomi keluarga. Tujuan dari penelitian ini menganalisis hubungan sosial ekonomi orang tua tunggal dengan frekuensi makan dan status gizi remaja. Populasi penelitian remaja (putra/putri) usia 14-16 tahun sebanyak 91 orang. Teknik sampling dengan simple random sampling. Kriteria inklusi adalah remaja (putra/putri) yang tidak tinggal di pondok, orang tua tunggal (ayah saja atau ibu saja). Sampel dalam penelitian 87 orang. Instrumen yang digunakan kuesioner singkat tentang data demografi (umur remaja, orang tua tunggal, penyebab orang tua menjadi tunggal, pendidikan orang tua, pekerjaan orang tua). Kuesioner untuk data khusus frekuensi makan dalam sehari. Lembar observasi untuk menganalisi berat badan dan tinggi badan remaja. Analisis data menggunakan Chi Square. Hasil penelitian menunjukkan diperoleh nilai p=0,000 berarti ada hubungan antara sosial ekonomi orang tua tunggal dengan frekuensi makan remaja dan p=0,003 berarti ada hubungan antara sosial ekonomi orang tua tunggal dengan status gizi remaja. Kata kunci : Sosial Ekonomi, Orang Tua Tunggal, Frekuensi Makan, Status Gizi Remaja